Wpływ zastosowania rachunku kosztów docelowych na mierniki strategicznej karty wyników - Masztalerz, Marek (The impact of target costing on the balanced scorecard measures, 2006)
The paper describes the influence of target costing on the fundamental measures used in the Balanced Scorecard and shows how target costing influences the four perspectives of Balanced Scorecard. The impact of target costing on most popular indicators is considered and analyzed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 258-267